Enterovirus A71 infection-induced dry eye-like symptoms by damaging the lacrimal glands - Zhou, Nan; Chen, Taige; You, Qiao; Chen, Deyan; Liu, Lifei; Hu, Kai (Frontiers in Cellular and Infection Microbiology, 2024)
To determine the effects of EV-A71 (Enterovirus A71) infection on ocular surface and its mechanism.AG6 mice aged two to three weeks were randomly divided into control and EV-A71 infected groups. Slit-lamp observation, fluorescein staining, and phenol red thread test were used to assess symptoms of ocular surface at 4 dpi (days post infection). The pathological changes of cornea and lacrimal gland were observed by H&E staining, PAS staining, TUNEL assay, IHC staining and qRT-PCR. Corneas and lacrimal glands from mice were obtained and processed for RNA sequencing analysis. Newly diagnosed HFMD patients caused by EV-A71 were recruited and ensured they met the inclusion criteria. Ocular surface parameters (TMH and NIKBUT) were measured using the OCULUS Keratograph 5M. Tear samples were taken to examine Cxcl1 and IL-6 levels through the ELISA method.Mice studies revealed that EV-A71 infection caused tear film instability, decreased tear secretions, decreased in lacrimal gland size, and distinct goblet cell loss. It also resulted in increased large vacuoles within acinar cells and structural damage in lacrimal gland. Apart from minor damage to the epidermis, there was no obvious inflammatory changes or apoptosis in the cornea. However, there were significant inflammatory injury and apoptosis in the lacrimal gland. RNA-seq analysis showed IL-17 and NF-κB signaling pathways were activated in the lacrimal glands of mice infected with EV-A71. In HFMD patients, the THM was in a low range and NITBUT was significantly shorter than the control group by Oculus Keratograph 5M. ELISA assay showed a higher tear Cxcl1 and IL-6 level in them.EV-A71 infection affected lacrimal gland structure and function and induced dry eye-like symptoms.